Entrepreneurial Mindset and Adaptation Capability in Business" - Hasyim; Fitri Ayu Hardiana Rambe; Gabriella Simanjuntak; Icha Henrie Novrianti Hutajulu (International Journal of Advanced Technology and Social Sciences, 2023)
The journal "Entrepreneurial Mindset and Adaptability in Business" discusses how entrepreneurship is crucial for Indonesia's economic growth, especially for the younger generation. The author emphasizes that the government is crucial in creating jobs by developing young entrepreneurs. The process of capitalizing on business opportunities by using innovation and creativity is known as entrepreneurship. To achieve this goal, entrepreneurship education focuses on teaching youth to build, own and manage their own businesses. The purpose of this research is to produce a business learning model that can last. Analysis of various entrepreneurship-related documents, laws and regulations, start-up guides, and previous research was used as the research method.  The results show that improving entrepreneurial literacy is essential to encourage Indonesian millennials to build their own businesses. In addition, it was mentioned that a company's ability to adapt is key to dealing with change.  Organizational leaders and managers play an important role in this. Participation is important in helping organizations change, and fostering entrepreneurial understanding among students is important to produce new entrepreneurs who are ready to face future challenges.So, entrepreneurship education is essential to shape the millennial generation who will become competitive entrepreneurs. This education prioritizes creativity, innovation and practical entrepreneurial skills. Students' ability and interest to build their own business is influenced by entrepreneurial literacy. An important step in developing new entrepreneurs who will transform Indonesia's economy and society is understanding the concept of entrepreneurship and a honed entrepreneurial spirit